A Walking Curriculum: From “Good Ideas for Walks” to Transformative Design for Eco-Social Change - Judson, Gillian; Datura, Michael (International Journal of Education Policy and Leadership, 2023)
This pilot implementation study examines the experiences of ten teachers who have employed a place-based learning resource called A Walking Curriculum for one to three years. A Walking Curriculum is an example of Imaginative Ecological Education—a pedagogical approach that centralizes imaginative engagement, emotional connection, and somatic understanding in place-based learning. Initially, researchers sought to understand teachers’ practices and to determine how (or if) A Walking Curriculum provided teachers with a deeper insight into the principles of Imaginative Ecological Education underlying it. The research focus shifted to the nature of professional development and the meaning of educational change in a more-than-human world. This article considers policy implications of an ecological model of educational change that might better align with the eco-social transformation intentions of Imaginative Ecological Education.